2008
DOI: 10.1007/s11069-008-9305-8
|View full text |Cite
|
Sign up to set email alerts
|

Building models for automatic landslide-susceptibility analysis, mapping and validation in ArcGIS

Abstract: In this paper, ModelBuilder TM in ArcGIS (ESRI) has been applied to landslidesusceptibility analysis, mapping and validation. The models (scripts), available for direct downloading as an ArcGIS tool, allow landslide susceptibility to be computed in a given region, providing a landslide-susceptibility map, with the GIS matrix method, and ensuring a quality validation. The paper details the steps needed for the model-building process, enabling users to build their own models and to become more familiar with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(27 citation statements)
references
References 31 publications
0
26
0
1
Order By: Relevance
“…Examples of previous studies Conditional analysis (CA) Clerici et al (2010, Conoscenti et al (2008, Costanzo et al (2012a, 2012b, Irigaray et al (2007), Jiménez-Peralvárez et al (2009), Rotigliano et al (2011, 2012, Vergari et al (2011) Discriminant analysis (DA) Baeza and Corominas (2001), Carrara (1983), Carrara et al (2008), Guzzetti et al (2006), Rossi et al (2010. ) Binary logistic regression (BLR) Atkinson and Massari (1998), Ayalew and Yamagishi (2005), Bai et al (2010), Can et al (2005), Carrara et al (2008), Chauan et al (2010), Conforti et al (2012), Dai and Lee (2002), Davis and Ohlmacher (2002), Erener and Düzgün (2010), Mathew et al (2009), Nandi and Shakoor (2009), Nefeslioglu et al (2008, Ohlmacher and Davis (2003), Van den Eckhaut et al (2006 Classification and regression trees (CART) Felicísimo et al (2012), Vorpahl et al (2012) Artificial neuronal networks (ANN) Aleotti and Chowdhury (1999), Ermini et al (2005), Lee et al (2004), Pradhan and Lee (2010) Original Paper exploited to compare the fitting of the model having only the constant term (all the β p are set to 0) with the fitting of the model that includes all the considered predictors with their estimated non-null coefficients so as to verify if the increase in likelihood is significant; in this case, at least one of the p coefficients is to be expected as different from zero …”
Section: Statistical Techniquementioning
confidence: 99%
“…Examples of previous studies Conditional analysis (CA) Clerici et al (2010, Conoscenti et al (2008, Costanzo et al (2012a, 2012b, Irigaray et al (2007), Jiménez-Peralvárez et al (2009), Rotigliano et al (2011, 2012, Vergari et al (2011) Discriminant analysis (DA) Baeza and Corominas (2001), Carrara (1983), Carrara et al (2008), Guzzetti et al (2006), Rossi et al (2010. ) Binary logistic regression (BLR) Atkinson and Massari (1998), Ayalew and Yamagishi (2005), Bai et al (2010), Can et al (2005), Carrara et al (2008), Chauan et al (2010), Conforti et al (2012), Dai and Lee (2002), Davis and Ohlmacher (2002), Erener and Düzgün (2010), Mathew et al (2009), Nandi and Shakoor (2009), Nefeslioglu et al (2008, Ohlmacher and Davis (2003), Van den Eckhaut et al (2006 Classification and regression trees (CART) Felicísimo et al (2012), Vorpahl et al (2012) Artificial neuronal networks (ANN) Aleotti and Chowdhury (1999), Ermini et al (2005), Lee et al (2004), Pradhan and Lee (2010) Original Paper exploited to compare the fitting of the model having only the constant term (all the β p are set to 0) with the fitting of the model that includes all the considered predictors with their estimated non-null coefficients so as to verify if the increase in likelihood is significant; in this case, at least one of the p coefficients is to be expected as different from zero …”
Section: Statistical Techniquementioning
confidence: 99%
“…Clerici et al 2006Clerici et al , 2010Chacón et al 2006;Conoscenti et al 2008;Del Monte et al 2002;Irigaray et al 2007;Jiménez-Pelvárez et al 2009). According to conditional analysis, the landslide probability of each UCU was estimated by computing its landslide density, given as fraction of unstable (BLIP) cells to total cells.…”
Section: Susceptibility Modelling and Validationmentioning
confidence: 99%
“…Pereira et al (2014) have found that most landslides occur during the wettest months, reflecting the importance of rainfall-triggering mechanisms. Landslides can cause serious damage to buildings and infrastructure, to the environment, and to human life (Devoli et al 2007;Jiménez-Perálvarez et al 2009;Lacasse et al 2010). Further, landslides in populated areas can create health consequences that exceed the local capacity to respond, increasing both mortality and morbidity from disasters (Keim 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The largest proportion of landslide risk analyses or landslide susceptibility analyses has had a technical approach focusing on the first part of the function, the hazard probability (P), by performing and developing methods for mapping landslide risk, stability analysis, and mechanisms triggering landslides (e.g., Guzzetti et al 2005aGuzzetti et al , 2006Guzzetti et al , 2012Jiménez-Perálvarez et al 2009;Melchiorre and Tryggvason 2015;Poli and Sterlacchini 2007;Roslee and Jamaluddin 2012;Salas-Romero et al 2015;Van Den Eeckhaut et al 2012). Potential landslide consequences (C i ) have not attained the same scientific interest despite the obvious importance it has on the estimated risk product (R).…”
Section: Introductionmentioning
confidence: 99%